The Essentials of Mathematics, K-6: Effective Curriculum, Instruction, and Assessment (Priorities in Practice) - Checkley, Kathy (Priorities in practice, 2006)
This book describes best practices for engaging elementary students in mathematics, from exploring numbers, patterns, and shapes to posing real-life problems that develop students' ability to reason and problem-solve.